Investigations of nanoscale helical pitch in smectic-C and smectic-C* phases of a chiral smectic liquid crystal using differential optical reflectivity measurements - VIJ, JAGDISH (My University, 2006)
Differential optical reflectivity DOR was used to study the temperature dependence of the short helical pitch in freestanding films of a liquid crystal compound. The experimentally measured DOR signal was fitted using Berreman?s 4 4 matrix method to get the pitch value in the smectic-C * SmC * phase. The results show continuous evolution of the pitch between the smectic-C* and SmC * phases. In SmC * , the pitch decreases as temperature increases and is found to level off at 16?1 smectic layers at the SmC * to smectic-A* transition.
PUBLISHED
Article number 011701
Keywords: Electronic & Electrical Engineering